ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA DITINJAU DARI SELF-EFFICACY SISWA PADA MATERI SISTEM PERSAMAAN LINEAR TIGA VARIABEL - Imaroh, Abidatul; Umah, Ulumul; Asriningsih, Tafsillatul Mufida (IKIP Siliwangi, 2021)
System of linear equations in three variables is a material in high school that is easy to relate to daily life problems. However, there are still findings that show students' difficulties and errors in solving the problems. Students' disbelief in their ability to solve problems is thought to be an obstacle for students, but further research is needed to prove it. This study aims to describe students' problem solving abilities on system of linear equations in three variables material their self-efficacy in terms of their self-efficacy towards their ability to solve mathematical problems. The subjects in this study were students of class X MAU Darul 'Ulum Jombang. The research method was a mixed of quantitative and qualitative. Quantitative methods are used to analyze data on the level of self-efficacy obtained through giving questionnaires to all students to determine the subject to be studied further. Qualitative methods were used to analyze test results and interview data on the problem-solving abilities of four students who were selected based on four categories of self-efficacy levels. The results showed that students who were in the higher self-efficacy category tended to have better problem solving abilities.